A inserç\~ao da agricultura familiar no Programa Nacional de Alimentaç\~ao Escolar: Impactos na renda e na atividade produtiva - Silvio da Rosa Paula; Regina Helena Rosa Sambuichi; Sandro Pereira Silva; Fabio Alves; Alexandre Arbex Valadares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This study analyzed the impacts produced by the rule for purchasing family farming products for the National School Feeding Program (PNAE). It sought to verify the effects that the change in the public food procurement (CPA) mechanism under this program caused on the income and productive activity of family farmers who were able to access this market at some point in time. To this end, the difference-in-differences econometric approach was used as an empirical strategy, combined with the entropy balancing technique - applied by cross-referencing the program's database with the Producer Aptitude Declaration (DAP) database. From the analysis carried out, it was found that the PNAE generates statistically significant economic effects on the income of family farmers who can access this market, although as for productive diversity the results were inconclusive. It is concluded that the PNAE is an important tool for raising the gross value of production for family agriculture, constituting an important component of a local development strategy.
Keywords: Q18; Q12; C23; 330; public purchases; school meals; family farming; impact assessment; sustainability